Causal recipes for customer loyalty to travel agencies: Differences between online and offline customers - Silva, Graça Miranda (2022)
This study investigates how travel agencies can achieve high customer loyalty through offline and online shopping experiences. The study testswhether different configurations of perceived value, customer satisfaction, perceived quality, and trust affect loyalty. The results froman online survey of a travel agency's 1974 offline and 1014 online customers provide the data. Using the fsQCA, the study finds that different combinations of these factors lead to higher customer loyalty. The findings show that trust is a sufficient condition for high customer loyalty only in the offline shopping context. In the online shopping context, travel agencies must combine trust with perceived value or with perceived quality to achieve high customer loyalty. Further, in the offline shopping context, the combination of perceived value and perceived quality leads to higher loyalty, while in the online shopping context agencies need to add customer satisfaction to this configuration.